The practice of nursing research : conduct, critique, and utilization - Burns, Nancy, Ph. D.; Grove, Susan K. (St. Louis, Mo. : Elsevier/Saunders, 2005)
"Practicing nurses, students, and instructors appreciate this book for its clear, direct writing style that makes complex concepts easy to understand; unique nursing perspective and framework that link nursing research to nursing practice; balanced and detailed coverage of both quantitative and qualitative research; and abundant, concrete examples from the best research literature."--BOOK JACKET.
1. Discovering the world of nursing research -- 2. The evolution of research in nursing -- 3. Introduction to quantitative research -- 4. Introduction to qualitative research -- 5. Research problem and purpose -- 6. Review of relevant literature -- 7. Frameworks -- 8. Objectives, questions, and hypotheses -- 9. Ethics in research -- 10. Understanding quantitative research design -- 11. Selecting a research design -- 12. Outcomes research -- 13. Intervention research -- 14. Sampling -- 15. The concepts of measurement -- 16. Measurement strategies in nursing -- 17. Collecting and managing data -- 18. Introduction to statistical analysis -- 19. Using statistics to describe variables -- 20. Using statistics to examine relationships -- 21. Using statistics to predict -- 22. Using statistics to examine causality -- 23. Qualitative research methodology -- 24. Interpreting research outcomes -- 25. Communicating research findings -- 26. Critical analysis of nursing studies -- 27. Using research knowledge to promote an evidence-based practice in nursing -- 28. Proposal writing for research approval -- 29. Seeking funding for research -- App. A. Table of random numbers -- App. B. Cumulative normal distribution (Z) -- App. C. Percentage points of student's t distribution -- App. D. Percentage points of the F distribution -- App. E. Critical values for the [chi][superscript 2] distribution -- App. F. Table of probabilities associated with values as small as observed values of U in the Mann-Whitney test -- App. G. Table of critical values of U in the Mann-Whitney test -- App. H. Percentiles of the Kolmogorov-Smirnov test statistic -- App. I. Table of critical values of r in the runs test -- App. J. Critical values for the Wilcoxon signed-ranks test (N=5[1]50) -- App. K. Table of probabilities associated with values as large as observed values of H in the Kruskal-Wallis one-way analysis of variance by ranks -- App. L. Table of probabilities associated with values as large as observed values of [Chi][superscript 2]in the Friedman two-way analysis of variance by ranks -- App. M. Statistical power tables ([Delta]=effect size).
Includes bibliographical references and index.
Keywords: Nursing -- Research -- Methodology; Nursing Research; Evidence-Based Medicine